PREDICTIVE VALUES OF PROCALCITONIN FOR SECONDARY BACTERIAL INFECTIONS IN PATIENTS WITH COVID-19 - Ergashov Maqsudjon Muzaffarovich, (TADQIQOTLAR, 2025)
ANNOTATION.  This  article  highlights  the  importance  of  C-reactive  protein (CRP) and procalcitonin (PCT), and cytokines in determining the prognosis of SARS-CoV-2-associated pneumonia. The article discusses the methods used to measure these biomarkers and the results of studies that have investigated their use in predicting the severity and outcome of SARS-CoV-2-associated pneumonia. The article concludes with  a  discussion  of  the  implications  of  these  findings  and  suggestions  for  future research.